ERROR ANALYSIS ON THE SPOKEN ENGLISH OF FBIB STUDENTS: A PRELIMINARY RESEARCH - Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2008)
A study on error in English language use has long been conducted by different researchers and in different settings (Richards 1971; Nemser 1971; Selinker 1972; Brown 1994; Ellis 1995). Different English educational institutions continuously conduct similar studies mainly because they do not only want to identify linguistic problems encountered by their students and to account for their language development but they also want to benefit from the necessary information they may use to better the learning materials (Farooq 1998; Bartlett 2002). In this study the writer investigated grammatical errors as encountered in students’ spoken English. Thirty English students of the Faculty of Language and Cultural Studies Stikubank University were randomly asked to speak about any issue they were interested in. This was recorded and the data were transcribed and categorized under (1) the type of grammatical errors, (2) problem areas, (3) Selinker’s error categories (1972) and (4) semantic impacts. The most problems encountered by the students are as follows: verb phrase (24.6%), syntax (78.7%), transfer of training and strategy of language learning (77.1%) and local semantic impact (92.6%). Key words: grammatical error, error category, problem area, semantic impact